1993
DOI: 10.1128/jcm.31.4.947-954.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of portions of the 34-kilodalton-protein gene of Mycobacterium paratuberculosis: its application to serological analysis of Johne's disease

Abstract: Paratuberculosis (Johne's disease), an endemic mycobacteriosis of cattle that is caused by Mycobacterium paratuberculosis, is characterized by incoercible diarrhea and fecal shedding of bacteria. The present work aimed at developing a specific serological test for this disease. We have recently shown that a 34-kDa protein belonging to the major antigen complex A36 of M. paratuberculosis is immunodominant and contains epitopes specific with respect to all mycobacteria tested, including Mycobacterium bovis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 26 publications
4
23
1
1
Order By: Relevance
“…1, tracks 8,9,10) or anti-bovine tuberculin-PPD ( Fig. 1, tracks 11,12,13). Most of these bands present in the patterns of the three organisms are presumably re- paratuberculosis 2E (lanes 2, 5, 8, 11), M. avium D4 (lanes 3, 6, 9, 12) and M. boris BCG (lanes 4, 7, 10, 13) were fractionated by polyacrylamide gel electrophoresis (SDS-12% PAGE) and transblotted to a nitrocellulose membrane.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1, tracks 8,9,10) or anti-bovine tuberculin-PPD ( Fig. 1, tracks 11,12,13). Most of these bands present in the patterns of the three organisms are presumably re- paratuberculosis 2E (lanes 2, 5, 8, 11), M. avium D4 (lanes 3, 6, 9, 12) and M. boris BCG (lanes 4, 7, 10, 13) were fractionated by polyacrylamide gel electrophoresis (SDS-12% PAGE) and transblotted to a nitrocellulose membrane.…”
Section: Resultsmentioning
confidence: 88%
“…To the sec- ond group were assigned the 49.8-and 38.3-kDa proteins of M. avium and the 58.7-and 54.0-kDa proteins of M. bovis, which are endowed with at least one species-specific epitope with respect to the other two mycobacteria. Screening procedures based on antisera pre-adsorbed on heterologous bacterial sonicates were previously found to be very useful to identify proteins endowed with species-specific epitopes in complex protein mixtures [11,12]. By the combined approach used in this work, several cross-reactive proteins (presumably responsible for the non-specificity of tuberculin-like assays) and a few proteins endowed with at least one species-specific epitope (putative reagents for specific cutaneous tests) were identified.…”
Section: Resultsmentioning
confidence: 98%
“…Genomic DNA was extracted as previously described [9]. All other DNA manipulations were carried out by standard methods [10].…”
Section: Dna Manipulation and Sequence Analysismentioning
confidence: 99%
“…The aminoterminal hydrophobic region is buried within the bacterial envelope, whereas the hydrophilic carboxyterminal is exposed at the cell surface [14]. In addition, the B-cell epitopes at the C-terminal region were localized by immune electron microscopy to the cell surface [15]. Using a panel of sera from cattle, naturally infected with tuberculosis or paratuberculosis, De Kesel et al [15] concluded that the 98-amino acid carboxyterminal region of p34 is specific for M. paratuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the B-cell epitopes at the C-terminal region were localized by immune electron microscopy to the cell surface [15]. Using a panel of sera from cattle, naturally infected with tuberculosis or paratuberculosis, De Kesel et al [15] concluded that the 98-amino acid carboxyterminal region of p34 is specific for M. paratuberculosis. This observation was consistent with the reactivity of serum from rabbits immunized with this polypepetide.…”
Section: Introductionmentioning
confidence: 99%